A Delphi consensus study to identify current clinically most valuable orthopaedic anatomy components for teaching medical students - Swamy, Meenakshi (BMC Med Educ, 2014)
BACKGROUND: Over recent years, wide ranging changes have occurred in undergraduate medical curricula with reduction of hours allocated for teaching anatomy. Anatomy forms the foundation of clinical practice. However, the challenge of acquiring sufficient anatomical knowledge in undergraduate medical education for safe and competent clinical practice remains. The purpose of this study is to identify clinically most valuable orthopaedic anatomy components that are relevant to current clinical practice in order to reinforce anatomy teaching. METHODS: Modified Delphi technique with three rounds involving twenty currently practicing orthopaedic consultants and senior speciality orthopaedic registrars (StR, year six and above) was conducted. Anatomical components applied in corresponding clinical situations were generated from the opinions of this expert panel in the first round and the clinical importance of each of these components were rated with a four point Likert scale in the subsequent two rounds to generate consensus. Percentage agreement was utilised as outcome measure for components rated as considerably/very important with consensus of more than 94%. RESULTS: Response rates were 90% for the first round and 100% for the next two rounds. After three Delphi rounds, thirty four anatomy components applied in general/ specific clinical conditions and clinical tests were identified as clinically most valuable following iteration. CONCLUSIONS: The findings of this study provide clinicians opinions regarding the current required essential anatomical knowledge for a graduating medical student to apply during their orthopaedic clinical encounters. The information obtained can be utilised to encourage further development of clinical anatomy curriculum reflecting the evolving nature of health care.